1976
DOI: 10.1080/00071667608416316
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary vitamin a, ascorbic acid and their interaction on turkey bone mineralisation1

Abstract: At early ages, added dietary ascorbic acid did not affect growth or femur mineralisation of poults. In poults after 8 and 12 weeks, femur mass was reduced by 3000 mg ascorbic acid per kg diet. 2. Plasma calcium and magnesium were not influenced differently by 1000, 4000 and 16,000 IU vitamin A/kg diet, but plasma phosphorus was decreased by the 16,000 level. 3. Vitamin A at 1000 or 16,000 IU/kg diet reduced growth in both sexes to 12 weeks of age compared with the NRC recommended 4000 IU/kg diet. In males, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1978
1978
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Further, shell thickness influences the egg shell weight, which is the cause of significant shell weight differences (p<0.05) recorded between the groups in the present study. In birds, L-AA augments conversion of 1,25 dihydoxycholecalciferol in the kidney and increases calcium mobilization from skeleton which suggests its role in egg shell formation and strength (Dorr and Balloun, 1976; Bollengier-Lee et al, 1999). Besides, the content of organic matrix in the shell is positively correlated to the available ascorbic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Further, shell thickness influences the egg shell weight, which is the cause of significant shell weight differences (p<0.05) recorded between the groups in the present study. In birds, L-AA augments conversion of 1,25 dihydoxycholecalciferol in the kidney and increases calcium mobilization from skeleton which suggests its role in egg shell formation and strength (Dorr and Balloun, 1976; Bollengier-Lee et al, 1999). Besides, the content of organic matrix in the shell is positively correlated to the available ascorbic acid.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that ascorbic acid plays arole in bone maturation by improving hydroxyproline production which is required for collagen formation. Accordingly, in birds it was postulated that ascorbic acid stimulates 1, 25dihydroxy cholecalciferol and together with it in increases calcium mobilization from bones, suggesting vitamin C has an important role in egg shell formation (Dorr and Balloun, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…Sahin and Onderci (2002) detailed that a diet blend of vitamin C at level 250 mg/kg and Cr at level 400 μg gives the most raised useful results on the exhibition and egg quality attributes of laying birds under a low temperature. Dorr and Balloun (1976) reported that in birds, it had proposed that vitamin C corrosive animates 1, 25-dihydroxycholecalciferol and alongside it increments calcium arranging from bones, recommending that vitamin C has a colossal effect in eggshell course of action. The aim of this research is to study the effect of using chromium chloride or L-carnitine either alone or with vitamin C during heat stress in the summer on egg production and egg quality of Golden Montazah hens.…”
Section: Inmentioning
confidence: 99%